Differentiation-Induced Uroplakin III Expression Promotes Urothelial Cell Death in Response to Uropathogenic E. coli - Thumbikat, Praveen (2008)
Uropathogenic E. coli (UPEC) expressing type 1 pili underlie most urinary tract infections (UTIs). UPEC adherence to the bladder urothelium induces a rapid apoptosis and exfoliation of terminally-differentiated urothelial cells, a critical event in pathogenesis. Of the four major uroplakin proteins that are densely expressed on superficial urothelial cells, UPIa serves as the receptor for type 1-piliated UPEC, but the contributions of uroplakins to cell death are not known. We examined the role of differentiation and uroplakin expression on UPEC-induced cell death. Utilizing in vitro models of urothelial differentiation, we demonstrated induction of tissue-specific differentiation markers including uroplakins. UPEC-induced urothelial cell death was shown to increase with enhanced differentiation but required expression of uroplakin III: infection with an adenovirus encoding uroplakin III significantly increased cell death, while siRNA directed against uroplakin III abolished UPEC-induced cell death. In a murine model of UTI where superficial urothelial cells were selectively eroded to expose less differentiated cells, urothelial apoptosis was reduced, indicating a requirement for differentiation in UPEC-induced apoptosis in vivo. These data suggest that induction of uroplakin III during urothelial differentiation sensitizes cells to UPEC-induced death. Thus, uroplakin III plays a pivotal role in UTI pathogenesis.